A Section Through the Nanga Parbat Syntaxis, Indus Valley, Kohistan - Coward, M.P. (Journal of Himalayan Earth Sciences, 1985)
The Nanga Parbat gneisses show polyphase Himalayan age deformation, the last major phase being the development of large upright folds which form the syntaxial structure. These folds are related to a different kinematic system to the main thrust systems of Pakistan and probably formed due to localised high strain near the pinning point of the Himalayan thrusts at the western end of the Himalayan arc.